CRITERIA OF WELL-DIFFERENTIATED THYROID CARCINOMA RESISTANCE TO RADIOIODINE THERAPY - P. O. Rumyantsev; D. K. Fomin; U. V. Rumyantseva (Опухоли головы и шеи, 2015)
In patients with well-differentiated thyroid cancer (WDTC) recurrence the metastatic tumor foci in numerous cases are not responded to radioiodine therapy which seriously deteriorate survival prognosis. In this article the contemporary evidential basis is analyzed so as to determine criteria of the resistance to radiodiodine therapy in inoperable WDTC patients.